Pluralism in economics: Inquiries into a Daedalean concept - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2016)
The state of contemporary economics had been a subject of discussion even before the most recent global financial crisis. The one-sidedness of the discipline has frequently been lamented and calls are often made for its pluralisation. Nevertheless, there is neither a consensus over the form of pluralism that is required (whether this is a theory, method, or paradigm pluralism, for example), nor agreement among economists over the underlying diagnosis of a lack of pluralism. Even the justification for this pluralistic norm - i.e. whether it should be seen in terms of an ethics of fairness and tolerance or as the imperative of academic freedom - remains disputed and is often unclear. The present paper aims to shed some light on these ambiguities.
Keywords: B40; B41; B50; 330; pluralism; philosophy of science; heterodoxy; orthodoxy; mainstream